Alternative food sources interfere with removal of a fungal amphibian pathogen by zooplankton. Issue 12 (28th September 2021) - Deknock, Arne; Pasmans, Frank; van Leeuwenberg, Robby; Van Praet, Sarah; Bruneel, Stijn; Lens, Luc; Croubels, Siska; Martel, An; Goethals, Peter
Abstract: While the amphibian disease chytridiomycosis is causing ongoing population declines and biodiversity losses around the globe, efficient mitigation strategies are lacking. The free‐living zoospores of the causative agents of this disease, the chytrid pathogens Batrachochytrium dendrobatidis (Bd) and Batrachochytrium salamandrivorans (Bsal), are a potential food source for filter‐feeding micropredators as part of the aquatic food web. While consumption of zoospores can lower environmental pathogen loads, alternative food sources may interfere with pathogen removal rates. We compared the ability of three filter‐feeding zooplankton species, the cladoceran Daphnia magna, the rotifer Brachionus calyciflorus and the ostracod Heterocypris incongruens, to remove Bd zoospores in water and investigated the effect of alternative food sources, the green algae Pseudokirchneriella subcapitata and Chlorella vulgaris, on zoospore ingestion by D. magna . Daphnia magna was the only micropredator candidate that effectively removed Bd zoospores from its environment, with an average removal rate of 1, 012 ± 542 GE ind. −1 hr −1 within our test system. High concentrations (1 × 10 5 cells/ml) of large and easily ingestible P. subcapitata reduced pathogen removal rates, whereas the small and less edible C. vulgaris did not interfere with pathogen removal. Synthesis and applications . We showed that Daphnia spp., which are keystone species in all sorts of aquatic habitats worldwide, are promising target agents for biologically mitigating chytridiomycosis infections and how natural food sources may interfere with this strategy. We also suggest potential management actions for biological disease mitigation, aiming to optimize environmental conditions for these target filter feeders, thereby reducing pathogen densities and eventually infection pressure in amphibian hosts. Examples of such management actions include, but are not limited to, removal of planktivorous fish, habitat restoration, nutrient control or agrochemical regulation in the vicinity of amphibian breeding ponds. Further studies, including field trials, are needed to confirm the effects of pathogen consumption on infection dynamics in natural situations and investigate the impact of intervention actions. Abstract : We showed that Daphnia spp., which are keystone species in all sorts of aquatic habitats worldwide, are promising target agents for biologically mitigating chytridiomycosis infections and how natural food sources may interfere with this strategy. We also suggest potential management actions for biological disease mitigation, aiming to optimize environmental conditions for these target filter feeders, thereby reducing pathogen densities and eventually infection pressure in amphibian hosts. Examples of such management actions include, but are not limited to, removal of planktivorous fish, habitat restoration, nutrient control or agrochemical regulation in the vicinity of amphibian breeding ponds. Further studies, including field trials, are needed to confirm the effects of pathogen consumption on infection dynamics in natural situations and investigate the impact of intervention actions. Samenvatting: Terwijl de amfibieziekte chytridiomycose wereldwijd populatieafnames en biodiversiteitsverlies veroorzaakt, ontbreekt het nogsteeds aan doeltreffende mitigatiestrategieën. Vrijlevende zoösporen van deziekteverwekkers, de Chytridiomycota Batrachochytrium dendrobatidis (Bd) en Batrachochytriums alamandrivorans (Bsal), zijn een mogelijke voedselbron voor filtrerende micropredatoren die deel uitmaken van het aquatische voedselweb. Hoewel predatie op zoösporen de aanwezigheid van pathogenen kan reduceren, kunnen alternatieve voedselbronnen deze predatie‐interactie verstoren. Wij vergeleken het vermogen van drie filtervoedende organismen uit de zoöplanktongemeenschap, nl. de Cladocera Daphnia magna, derotifer Brachionus calyciflorus en de ostracod Heterocypris incongruens, om Bdzoösporen te verwijderen uit water en onderzochten het effect van alternatievevoedselbronnen, de groene algen Pseudokirchneriella subcapitata en Chlorellavulgaris, op de opname van zoösporen door D. magna . D. magna was de enige kandidaat micropredator dat Bd zoösporen kon verwijderen uit zijn omgeving, met een gemiddelde verwijderingssnelheid van 1, 012 ± 542 GE ind. −1 hr −1 in onze proefopzet. Hoge concentraties (1 × 10 5 cellen/ml) van de grote en makkelijk opneembare cellen van P. subcapitata verlaagden de verwijderingssnelheid van pathogene sporen, terwijl de kleine en minder eetbare cellen van C. vulgaris geen interactie vertoonden met het verwijderen van zoösporen. Synthese en toepassingen . Wij tonen aan dat Daphnia spp., die een cruciale rol hebben in verschillende soorten aquatische ecosystemen wereldwijd, een veelbelovende doelgroep is voor biologische mitigatie van chytridiomycose infecties en hoe natuurlijke voedselbronnen deze strategie kunnen verstoren. Daarnaast stellen we ook een aantal mogelijke ingrepen voor om milieucondities te optimaliseren voor deze micropredatoren en zo het aantal ziekteverwekkers en de infectiedruk op amfibieën te verlagen. Voorbeelden van dergelijke ingrepen zijn o.a. de verwijdering van planktivore vissen, habitatherstel, nutriëntenbeheer en gecontroleerd gebruik van agrochemicaliën in de nabijheid van voortplantingspoelen van amfibieën. Verder onderzoek, inclusief veldproeven, is noodzakelijk om het effect van de consumptie van zoösporen op infectiedynamieken te onderzoeken in natuurlijke situaties en de impact van menselijke ingrepen te onderzoeken.